Reproductive and developmental toxicology - Hoberman, Alan; Lewis, Elise (Henry Stewart Talks, 2009)
Assessing the risk of exposure to a new pharmaceutical is critical in providing information on the safe and effective use of any new product, Reproductive and developmental toxicology is the study of the potential adverse effect of a drug, chemical, consumer product or medical device on the ability of a male and female to produce healthy normal children, Adverse outcomes have lead to the safety testing that is mandated, The guidelines that outline the safety testing required, the principles that these guidelines are based on and the potential hazard assessments that are made are based on the test results
Archived at 2021/07/28